The influence of ameliorant, nutrient solution and bioferilizer on soil P, plant P uptake, and yield of red chili. - Fitriatin, Betty Natalie; Dupa, Putri Siska Ekayanti; Fauziah, Nicky Oktav; Wong, Mui-Yun; Simarmata, Tualar (Jurnal AGRO, 2024)
The productivity and quality of red chili are greatly influenced by soil conditions and the availability of nutrients. Nutrients play a critical role in the growth and development of red chili plants. This experiment aimed to determine the combination of ameliorant, nutrient solution, and biofertilizer on the population of phosphate-solubilizing bacteria (PSB), available P, P-uptake, and red chili production in Inceptisols. The experiment was conducted at the experimental field of the Faculty of Agriculture, Universitas Padjadjaran. The experiment used a Randomized Complete Block Design (RCBD) with seven treatments and four replications, consisting of control, NPK, and nutrient solution (NS) with doses of 0, 6, and 12 kg ha-1 biofertilizers. The dosage used in a single application was 15 g plant-1 of NPK fertilizer and 300 mL plant-1 of nutrient solution. The base fertilizer consisted of manure in the control treatment and an ameliorant in other treatments at a dose of 4 t ha-1. The results showed that the combination of ameliorant + NPK + 6 kg ha-1 biofertilizer increased PSB population (4.93 x 106 CFU mL-1), available P (15.4 ppm), and P-uptake (0.74 g plant-1). Meanwhile, the combination of ameliorant + nutrient solution + 6 kg ha-1 biofertilizer increased fruit diameter (15 mm), and length of red chili (17.3 cm). Correlation analysis indicated positive correlation between red chili production with stem diameter and fruit length, but a negative correlation with P-uptake. Regression analysis indicated that stem diameter and PSB population had the most dominant effect on red chili yield.Produktivitas dan kualitas cabai merah sangat dipengaruhi oleh kondisi tanah dan ketersediaan unsur hara. Unsur hara memegang peranan penting dalam pertumbuhan dan perkembangan tanaman cabai merah. Percobaan ini bertujuan untuk mengetahui kombinasi amelioran, larutan hara dan biofertilizer terhadap populasi bakteri pelarut fosfat (BPF), P tersedia, serapan P, dan produksi cabai merah pada tanah Inceptisols. Percobaan dilaksanakan di lahan percobaan Fakultas Pertanian Universitas Padjadjaran. Percobaan menggunakan Rancangan Acak Kelompok Lengkap (RAKL) dengan tujuh perlakuan dan empat kali ulangan, terdiri dari: kontrol, NPK dan Larutan Hara dengan dosis 0, 6, dan 12 kg ha-1 pupuk hayati. Dosis yang digunakan dalam satu kali aplikasi adalah pupuk NPK 15 g tanaman-1 dan larutan hara 300 mL tanaman-1. Pupuk dasar berupa pupuk kandang pada perlakuan kontrol dan amelioran pada perlakuan lain dengan dosis 4 t ha-1. Hasil penelitian menunjukkan bahwa kombinasi amelioran + NPK + 6 kg ha-1 pupuk hayati mampu meningkatkan populasi BPF (4,93 x 106 CFU mL-1), P tersedia (15,4 ppm), dan serapan P (0,74 g tanaman-1). Sementara itu, kombinasi amelioran + larutan hara + 6 kg ha-1 pupuk hayati mampu meningkatkan diameter buah (15 mm), dan panjang cabai merah (17,3 cm). Analisis korelasi menunjukkan korelasi positif antara produksi cabai merah dengan diameter batang dan panjang buah, tetapi korelasi negatif dengan serapan P. Analisis regresi menunjukkan bahwa diameter batang dan populasi BPF memiliki pengaruh paling dominan terhadap hasil cabai merah.